2020
DOI: 10.1186/s12984-020-00754-7
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality-based treatment for regaining upper extremity function induces cortex grey matter changes in persons with acquired brain injury

Abstract: Background Individuals with acquired brain injuries (ABI) are in need of neurorehabilitation and neurorepair. Virtual anatomical interactivity (VAI) presents a digital game-like format in which ABI survivors with upper limb paresis use an unaffected limb to control a standard input device and a commonplace computer mouse to control virtual limb movements and tasks in a virtual world. Methods In a prospective cohort study, 35 ambulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The repetitive tasks of the different games could favor brain plasticity. Different studies have suggested that non-immersive VR therapy produces improvements in UE motor function in patients with stroke and increases gray matter volume in the motor and premotor regions of the affected hemisphere and could be correlated with an improvement in motor skills in undamaged brain areas, suggesting plasticity changes related to imagining, planning, and performing motor tasks [ 93 ]. In recent studies, other non-immersive VR devices, such as Doctor Kinetic [ 94 ] and the Nintendo ® Wii gaming system [ 95 ], have proven effective in improving UE motor function in stroke patients, demonstrating that they are a good tool to be used in neurorehabilitation, although they are not superior to CT when used alone [ 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…The repetitive tasks of the different games could favor brain plasticity. Different studies have suggested that non-immersive VR therapy produces improvements in UE motor function in patients with stroke and increases gray matter volume in the motor and premotor regions of the affected hemisphere and could be correlated with an improvement in motor skills in undamaged brain areas, suggesting plasticity changes related to imagining, planning, and performing motor tasks [ 93 ]. In recent studies, other non-immersive VR devices, such as Doctor Kinetic [ 94 ] and the Nintendo ® Wii gaming system [ 95 ], have proven effective in improving UE motor function in stroke patients, demonstrating that they are a good tool to be used in neurorehabilitation, although they are not superior to CT when used alone [ 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main therapeutic effect of VR on upper limb motor activity is to increase the active range of motion (AROM) of the shoulder, elbow, and wrist [ 121 , 122 ]. Significant gray matter increases were detected by MRI with voxel-based morphometry in five brain areas: the tail of the hippocampus, the left caudate nucleus, the rostral cingulate zone, the depth of the central sulcus, and the visual cortex [ 122 ]. Furthermore, the gray matter volumes of motor, premotor, and supplementary motor cortices correlated positively with the power and AROM measured in motor tests [ 122 ].…”
Section: Virtual Reality For Neurorehabilitationmentioning
confidence: 99%
“…Significant gray matter increases were detected by MRI with voxel-based morphometry in five brain areas: the tail of the hippocampus, the left caudate nucleus, the rostral cingulate zone, the depth of the central sulcus, and the visual cortex [ 122 ]. Furthermore, the gray matter volumes of motor, premotor, and supplementary motor cortices correlated positively with the power and AROM measured in motor tests [ 122 ]. Interestingly, EEG recordings showed significantly increased EEG concentration (indicated by strong beta waves) in the frontopolar 2 (FP2) and frontal 4 (F4) areas, and enhanced brain activity (indicated by higher average wave frequency) in the frontopolar 1 (FP1) and frontal 3 (F3) areas in an upper-extremity training group using VR [ 123 ].…”
Section: Virtual Reality For Neurorehabilitationmentioning
confidence: 99%
“…Regarding possible compensatory hypertrophy, there have been many studies showing that when brain regions perform more tasks, they enlarge. [47][48][49][50][51][52][53][54][55][56][57][58][59][60] There are a few possible causes or subcategories of the hypothesized compensatory hypertrophy that are discussed below, including: 1) injured brain regions becomes more active and enlarge; 2) uninjured brain regions connected to the injured brain regions become more active and enlarge; and 3) the injured regions atrophied in the post-injury acute phase and later enlarged as recovery occurred.…”
Section: Theoretical Importance Of Abnormal Enlargementmentioning
confidence: 99%
“…This is supported by studies of patients with brain disorders showing that increased brain activity leads to brain enlargement. 47,55,59,60 Subhypothesis 2: uninjured brain regions account for the enlargement. This is indirectly supported by studies of people without brain disorders showing that increased brain activity leads to brain enlargement.…”
Section: Theoretical Importance Of Abnormal Enlargementmentioning
confidence: 99%